A prospective study of the relation of patient-reported outcome measures with lumbar disc surgery for herniated lumbar disc - Naik, Hitendra S; Ghosh, Samarendra Nath; Saha, Pradeep; Biswas, Parthasarathy (Nepal Journal of Neuroscience, 2021)
Introduction: The aim of this 6-month prospective study was to seek out the factors affecting surgical outcome, predictors of treatment response and their correlates in open discectomy for herniated lumbar disc. Methods and Materials: Eighty patients who fulfilled the required criteria were chosen. Socio-demographic, clinical data proforma, Visual Analogue Scale for pain (VAS), Japanese Orthopedic Association (JOA) Scale for subjective and objective pain related QoL, General Health Questionnaire-12 (GHQ-12) for screening mental health, Short Form-36 (SF-36) Health Survey for assessing Health-related Quality of Life (HRQOL) and Montgomery Asberg Depression Rating Scale (MADRS) for measurement of clinical depression were used at the preoperative stage and reassessed again at 1 month, 3 months and 6 months post-discectomy. Results: Postoperatively, VAS and JOA Scale scores continued to show improvement at each follow up (p<0.001). Majority of the SF-36 subscales showed significant improvement at 3-months and 6-months of the postoperative period. A significant correlation was seen between the duration of pain symptoms and depression scores at 6 months (rho 0.301 p<0.01). Baseline VAS score had a significant negative correlation with baseline Physical Functioning and General Health scores at 6 months. The duration and severity of pain symptoms before surgery predicted the depression scores at 6 months (adjusted R square 0.056 p<0.001) postoperatively. Conclusion: The discectomy procedure resulted in significant improvement in baseline subjective pain symptoms and overall HRQOL. Greater the duration and intensity of pain symptoms at baseline, greater was the depression scores and lesser was the SF-36 physical functioning and general health at 6-month postoperative period.